Book Monuments in the National Museum of the Republic of Tyva - M. S. Maadyr; Sh. R. Khorlushtay (Библиосфера)
One of the urgent problems of domestic librarianship is highlighted, namely, the composition and content of book monuments stored in regional centers. These include the Aldan-Maadyr National Museum of the Republic of Tyva, one of the subjects of the Siberian Federal District of the Russian Federation. In 2011 the rare book sector was created in the museum, which concentrates the book monuments. The purpose of the article is to analyze printed publications published in the Tuvan People’s Republic, and now are the part of the book monuments of the National Museum of the Republic. It describes their composition, content and state of preservation. Newspapers, magazines, books, brochures and other types of printed products issued in the Tuvan People’s Republic give an idea of the state of the book culture of the country existed for twenty-three years: from 1921 to 1944. It shows the origin of printing and its development and graphic basis of local book publishing, its thematic repertoire and other aspects. The article gives recommendations on treatment of printed publications of the Tuvan People’s Republic, which can help to expand the directions and topics of museum information, educational, educational activities intended for the general public.